Analysis of the Influence of Job Autonomy, Leadership Style, and Emotional Intelligence on Employee Well-Being in Gig Workers - Fatimah Malini Lubis; Tyahya Whisnu Hendratni; Feby Arma Putra; Sonya Sidjabat; Flora Grace Putrianti; Budi Akhmad Tarigan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines how job autonomy, leadership style, and emotional intelligence factors influence freelancers within the gig economy. I used a quantitative approach, conducting a survey of intentionally sampled 150 participants. These participants were gig workers for at least six months, engaged with customers or service users, and had a work schedule of roughly 20 hours a week. As the primary data collection tool, I used a validated five-point Likert scale questionnaire analyzed with a t-test, and reliability was checked by calculating Cronbach’s Alpha. Before regression analysis, I performed classical assumption testing including checks for normality, heteroscedasticity, and multicollinearity. The results of data processing indicate that the three independent variables jointly have a significant effect on worker well-being. Separately, each variable also shows a positive effect, meaning that greater job autonomy, better perceived leadership, and higher levels of emotional intelligence, lead to higher levels of well-being perceived by gig workers. These findings broaden theoretical understanding in the field of human resource management, particularly in non-traditional work contexts. In addition, these results can also be used as a practical reference by digital platform management in designing strategies that are more responsive to the welfare needs of freelancers in the digital economy era.